Evaluation of the agreement between TNM 7th and 8th in a population‐based series of cutaneous melanoma. (9th November 2018) - Crocetti, E.; Stanganelli, I.; Mancini, S.; Vattiato, R.; Giuliani, O.; Ravaioli, A.; Balducci, C.; Falcini, F.; Pimpinelli, N.
Abstract: Background: The 8th edition of TNM has introduced new rules for staging cutaneous melanoma. Objective: To compare TNM 7th and 8th editions in defining pathological stages of melanoma. Methods: A population‐based series of 1847 skin melanoma from Romagna cancer registry (Italy) incident during 2003–2012 has been used to measure the agreement (with Cohen's kappa) between TNM 8th and 7th editions in defining melanoma stage. Disease‐specific survival has been computed for each stage according to TNM 7th and 8th. Results: The agreement between the two TNM editions was quite good when considered on average (kappa = 70.7%), moderate for stage I (61.5%), nearly perfect for stage II (95.0%), but extremely poor for stage III (8.1%). The overall melanoma‐specific observed survival was 90.8% at 5 year and 88.9% at 10 year with a strong prognostic effect of stage. Conclusion: TNM 8th edition introduces several changes which do not seem really helpful in addressing the care of stage I melanoma and may complicate the definition and comparability of stage III.